Air Transport and Logistics in Pandemic Outbreak of Influenza A (H1N1) virus - Majić, Zvonimir; Jukić, Irena; Pavlin, Stanislav (Promet - Traffic&Transportation, 2012)
In April 2009, the WHO, (World Health Organization) evaluated the available data on the swine influenza A (H1N1), confirmed the outbreak and declared decision on raising the pandemic phase from five to six. IATA, (International Air Transport Association) invited the airlines to support WHO’s reference laboratories around the world in handling specimens should the outbreak expand further. The specimens shall be transported according to the regulations stipulated for acceptance and transportation of dangerous goods by air. The paper analyses the current infrastructural situation at the airports in Croatia, predispositions related to the trained staff and coordination procedures with the relevant institutions. The implementation of activities complying with the international regulations are suggested in order to conduct measures fighting the pandemic in Croatia.KEY WORDS: pandemic outbreak, regulation, recommendation, specimen, responsibilities, transportation and logistic for biological substances